Energy system contribution to 100-m and 200-m track running events - Duffield, R.; Dawson, B.; Goodman, C. (Journal of Science and Medicine in Sport, 2004)
While sprint track running events, lasting 10-25 secs, are characterised by an anaerobic metabolic dominance, no actual track running data exist which have quantified the relative energy system contributions. Using previous methods employed by our laboratory, including 'in race' measures of VO2, accumulated oxygen deficit (AOD), blood lactate concentration and estimated phosphocreatine degradation (La/PCr), the aerobic-anaerobic energy system contributions to 100-m and 200-m events were calculated. For the 100-m event, results indicated a relative aerobic-anaerobic energy system contribution (based on AOD measures) of 21%-79% and 25-75% for males and females respectively (9%-91% and 11%-89% based on La/PCr measures; p<0.05 for both genders for 100-m from AOD estimates). For the 200-m, a 28%-72% and 33%-67% contribution for male and female athletes was estimated (21%-79% and 22%-78% based on La/PCr measures; NS from AOD estimates). A range of energy system contribution estimates for events of these durations have previously been proposed using a variety of techniques. The data from the current study also show different results depending on the measurement technique utilised. While AOD measures are often used to estimate anaerobic energy contribution, at such high exercise intensities (and brief exercise durations) as used in the present study, AOD measures showed larger aerobic energy estimates than expected.